Manutenção dos recursos naturais na floresta nacional do bom futuro e seu entorno, Rondônia, Brasil - Novais, Juliene Moreira; Mendonça, Andreza Pereira; Marinho, Lorena Lorrayne Estevão; Corti, Adrielen Moraes; Ferreira, Raissa Fonseca (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
In Brazil are recorded 65 National Forests (Flonas), with 32 of these located in the Amazon , representing 3.13% of total federal units that region. In Rondônia,3 Flonas were created (Bom Futuro, Jamari e Jacundá), and there is little information on the conservation status of these units. Thus, the overall objective was to avaliate the maintenance of natural resources in Flona Bom Futuro and its surroundings, located in the northwestern portion of the state of Rondônia, in the periods 1986-2011 through geoprocessing. The digital image processing, obtaining landscape metrics and location of the area were made using the software Processing Geographic Information Systems (Spring), version 5.1.8 that is available for free by the Institute for Space Research - INPE of Brazil website <http://www.dpi.inpe.br/spring/> and gvsig , version 1.9, obtaining data mapping on a scale of 1: 50000. It was used the model of the Earth South American Datum (SAD- 69) and the Universal Transverse Mercator Projection System (UTM). The entire procedure for calculation of areas was performed with the buffer zone of 10km, thus the information represented 606.000ha plan for the first three years analyzed (1986 , 1996 and 2006 ) and approximately 389.576ha for the year 2011 , due to reduction Flona. The study showed an increasing of anthropogenic fires and occupation, due to decreased vegetation. Also showed that the reduction of Flona not contributed to the maintenance of natural resources.